Application for Wakalah bi al-Ujrah Contract in Various Banks, Insurance, and Syariah Mutual Funds Indonesia According to Wahbah Zuhaili - Ghozali, Mohammad; Jamilah, Adinda Muftiviany Nur; Jamal, Mulyono; Hidayat, Iman Nur (AL- IKTISAB Journal of Islamic Economic Law, 2021)
Wakalah is one of the most frequently used transactions in insurance, mutual funds, and especially Islamic banking. Insurance is one of the economic activities that we often hear about, many of these activities, such as health insurance, education, and etc. This paper uses a literature analysis method by using journals as its primary source. According to Wahbah Zuhaili there is insurance that is allowed to do and there is insurance that is illegal to do. Basically, the purpose of the insurance is having a mutual help. So if the participant does not use the insurance premium they have been paid, this premium will be allocated to others. Until there is a help-seeking action based on sincerity. However, it will be illegal if the purpose of this insurance activity is based solely on profit. Thus, it will create a synergy that will eliminate the benefits. So this insurance being an illegal activity. which is containing five elements, there are riba, gharar, gaban, qimar, and jahalah, which can damage human benefits and harms. Then insurance activity is illegal.